Aluminum alloy brazing composite material, Al-Zn-based embedded brazing flux plate blank and preparation method of Al-Zn-based embedded brazing flux plate blank
By designing dislocations and pre-embedding of fluorine-containing flux in aluminum alloys, the Al-Zn-based embedded flux layer is formed, the problem of insufficient diffusion of Mg elements is solved, and the high yield strength and corrosion resistance after welding is achieved, and the overall performance of aluminum alloy brazed composite materials is improved.
Patent Information
- Application Number
- CN202411797809.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-11
AI Technical Summary
During the high-temperature brazing process of existing aluminum alloy brazing composites, the Mg element diffusion is insufficient, resulting in a decrease in the quality of the welded joints and it is difficult to achieve both high yield strength and corrosion resistance after welding.
By designing dislocations in the aluminum alloy structure and pre-embedding of fluorine-containing flux in the Al-Zn-based alloy, an Al-Zn-based embedded flux layer is formed. The dislocation channel is used to effectively diffuse the flux and Mg elements, forming KMgF3 substances to prevent the excessive diffusion of Mg elements and improve welding quality.
It realizes effective utilization of Mg elements under high-temperature brazing conditions, improves post-weld yield strength and corrosion resistance, reduces flux residues, and reduces production costs.
Smart Images

Figure CN119589197A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aluminum alloys, and in particular to an aluminum alloy brazing composite material, an Al-Zn-based pre-embedded brazing flux slab and a preparation method thereof. Background Art
[0002] As an important component of the power battery of new energy vehicles, the water cooling plate generates different amounts of heat in the battery pack due to the different positions and working conditions of the battery cells. If the temperature of the battery pack is inconsistent, it will affect the performance and life of the entire battery pack. By setting up the water cooling plate components, the coolant can be evenly distributed in the battery pack, so that the temperature of each battery cell remains relatively consistent, improving the overall performance and life of the battery pack. Secondly, the water cooling plate has better structural support and protection. The water cooling plate is usually installed inside or outside the battery pack, playing a certain structural support role, which can enhance the overall structural strength of the battery pack and protect the battery from external impact and vibration.
[0003] As a structural part, the requirements for the post-weld yield strength of the water-cooling plate are constantly increasing. The higher the post-weld yield strength, the better the structural support stability of the water-cooling plate for the battery. At present, the yield strength of some water-cooling plate materials after brazing aging can reach more than 150MPa, and still require good corrosion resistance. The strength level of the 3xxx series aluminum alloy water-cooling plate material used in traditional new energy vehicle battery water-cooling plates is low and it is difficult to meet the current application requirements.
[0004] In order to improve the post-weld yield strength, those skilled in the art control the addition of Mg, Si and Mg / Si to 6xxx aluminum alloy, and have obtained the post-weld yield strength that meets the requirements. For example, the composite plate disclosed in CN114670510A has a core layer material with Mg2Si as the main strengthening mechanism. Due to the large diffusion coefficient of Mg, Mg is easy to diffuse to the AlSi brazing material layer during high-temperature brazing, which not only reduces the Mg content in the core material. At the same time, if more Mg diffuses to the surface of the AlSi brazing material layer and reacts with the brazing agent, the effect of the brazing agent on the removal of the oxide film on the surface of the aluminum material will be reduced, the quality of the weld joint will be deteriorated, and the product will be scrapped. Therefore, the researchers have to increase the thickness of the barrier layer and suppress the Mg element within the barrier layer to ensure the quality of the welded joint. Therefore, the conventional structure of the composite plate is to provide a barrier layer on the surface of the core layer on the brazing side, and to achieve welding and bonding with other components by adding brazing material.
[0005] At present, water-cooled plates pursue performance in some extreme environments, which puts forward new requirements for corrosion resistance. In some harsh working environments, such as contact with corrosive coolants or in high humidity environments, aluminum alloys may corrode. In order to improve the corrosion resistance of water-cooled plate materials, an Al-Zn barrier layer is often set on the side prone to corrosion. With the potential difference between the Zn-containing layer and the core material, it acts as an anode and preferentially corrodes the Zn-containing barrier layer, thereby increasing the service life of the water-cooled plate material.
[0006] The prior art has a method of sequentially arranging a brazing material layer-embedded brazing flux layer-barrier on one side or both sides of the core material to replace the traditional method of adding brazing material, so that the composite plate introduces a brazing functional layer to realize the multifunctionality of the composite plate and simplify the subsequent brazing process. The brazing functional layer composed of the brazing material layer-embedded brazing flux layer is a relatively mature technology, and reference can be made to CN118616961A. However, after adding a brazing functional layer to such a composite plate, the original one-layer skin material composite is changed to a three-layer skin material composite, namely, the brazing material layer-embedded brazing flux layer-Al-Zn barrier layer-core layer. In order to realize the brazing function, the brazing material layer-embedded brazing flux layer obviously needs to occupy a certain thickness, which will cause the thickness ratio of the core layer to decrease. The core layer is the functional layer that contributes to the strength value in the composite plate, and the thickness ratio of the core layer directly affects the post-weld yield strength of the composite plate. Therefore, under the condition that the total thickness of the water-cooled plate material is certain, in order to achieve brazing and meet the corrosion resistance requirements, the thickness of the core material can only be sacrificed, which will undoubtedly seriously reduce the strength of the entire aluminum alloy brazing composite material. Summary of the invention
[0007] In view of the deficiencies in the prior art, the purpose of the present invention is to provide an aluminum alloy brazing composite material, an Al-Zn-based pre-embedded brazing flux slab and a preparation method thereof. Specifically, the brazing flux particles of the traditional pre-embedded brazing flux material are distributed in the aluminum silicon brazing material. When an Al-Zn alloy with a high solidus temperature is used as the matrix of the pre-embedded brazing flux, it is usually difficult to achieve the brazing function compared to an Al-Si alloy with a low liquidus temperature as the matrix of the pre-embedded brazing flux. This is because during brazing, the brazing flux needs to diffuse to the brazing surface to break the oxide film to achieve an effective welding joint, and the Al-Zn alloy has not yet melted at the brazing temperature, which seriously hinders the diffusion of the internal pre-embedded brazing flux to the surface. It is worth noting that, unlike the traditional pre-embedded method, the present invention achieves good brazing by distributing the brazing flux in the relatively high melting point Al-Zn alloy.
[0008] The present invention designs a certain amount of dislocations in the aluminum alloy structure, and dislocations are high-energy defect channels. Since the Zn content is within a certain range, the Al-Zn alloy is a material with high solidus temperature characteristics. At the brazing temperature, the Al-Zn alloy does not melt, which is not conducive to the flux in the Al-Zn-based pre-embedded flux layer to diffuse to the brazing surface. When there are many dislocations in the structure, the flux can use the dislocation channel to reach the brazing material layer.
[0009] During brazing, the Mg element of the core layer tends to diffuse to the surface, and the diffusion of the Mg element to the surface needs to pass through the Al-Zn-based pre-embedded flux layer. The Al-Zn-based pre-embedded flux layer in the technical solution of the present invention contains abundant high-energy dislocations, so the Mg element of the core layer tends to diffuse to the surface with the help of dislocations in the organization. It is known that the Mg element will react with the fluoride flux to consume the flux amount, but the inventor unexpectedly found that the reaction product of the Mg element and the fluorine-based flux can effectively block the diffusion of the Mg element to the brazing surface. During brazing, KMgF3 substances are formed in the dislocations on one side of the Al-Zn-based pre-embedded flux layer close to the core layer. The reactant has a strong ability to block the diffusion of the Mg element to the surface, and can effectively block the Mg element in the subsequent core layer from continuing to diffuse to the surface through dislocations, so that the Mg element content in the core layer is basically not lost. On the one hand, it can prevent the magnesium element from diffusing to the surface to cause brazing failure, and on the other hand, more Mg2Si aging strengthening phases can be obtained when the product is aged after brazing to improve the yield strength of the material after post-welding aging.
[0010] During brazing, a large amount of unreacted brazing flux on the side of the Al-Zn-based pre-embedded brazing flux layer close to the brazing material layer can diffuse along the dislocations to the brazing surface to break the surface oxide film.
[0011] To achieve this object, the present invention adopts the following technical solutions:
[0012] In a first aspect, the present invention provides an aluminum alloy brazing composite material, the aluminum alloy brazing composite material comprises a non-brazing material layer and a brazing material layer in sequence; the non-brazing material layer comprises a core layer and an Al-Zn-based pre-embedded brazing flux layer in sequence, the Al-Zn-based pre-embedded brazing flux layer is arranged close to the brazing material layer; the Al-Zn-based pre-embedded brazing flux layer comprises an Al-Zn alloy and a fluorine-containing brazing flux; the Al-Zn alloy comprises 1-12wt% of a Zn element according to a mass fraction, the Al-Zn-based pre-embedded brazing flux layer has a dislocation, and the dislocation density of the Al-Zn-based pre-embedded brazing flux layer is 2.5-4.0×10 14 / m 2 ; The non-solder layer cannot melt during brazing.
[0013] It is well known that the Zn element in Al-Zn aluminum alloy has the function of significantly reducing the potential of the aluminum alloy, thereby protecting the core material from being corroded too quickly. However, the solidus temperature of Al-Zn alloys is usually high, generally above 610°C. In conventional cognition, such high melting point alloys are not suitable as the matrix of the pre-embedded flux. Therefore, the present invention controls the dislocation density in the Al-Zn based pre-embedded flux layer to be between 2.5 and 4.0×10 14 / m 2 . When the dislocation density is too low, it will make it difficult for the embedded flux to reach the surface during brazing to effectively break the oxide film, which will lead to brazing failure. During brazing, the brazing material in the Al-Zn-based embedded flux layer reacts with the Mg in the core layer near the core material interface to generate KMgF3 substance, which blocks the diffusion of the core layer Mg to the embedded flux layer, effectively reducing the loss of Mg element in the core material. The core material generates more Mg2Si aging strengthening phases during the subsequent aging treatment process to improve the yield strength of the material after post-welding aging. When there are too many dislocations, it will be difficult to fully restrict the diffusion channel of the core layer Mg in the early stage of brazing, which will lead to excessive loss of Mg in the core material. In severe cases, it will cause a large amount of Mg to diffuse to the surface and cause brazing failure.
[0014] Al-Zn alloys cannot be melted during brazing, which makes them unsuitable for the matrix material of pre-embedded flux. Therefore, the present invention controls the dislocation density in the Al-Zn-based pre-embedded flux layer to be between 2.5 and 4.0×10 14 / m 2 , thus having a better brazing effect.
[0015] Specifically, the dislocation density of the Al-Zn based pre-embedded flux layer is 2.5 to 4.0×10 14 / m 2 , for example, it can be 2.5×10 14 / m 2 , 2.7×10 14 / m 2 , 2.9×10 14 / m 2 , 3×10 14 / m 2 , 3.2×10 14 / m 2 , 3.4×10 14 / m 2 , 3.5×10 14 / m 2 , 3.7×10 14 / m 2 , 3.9×10 14 / m 2 or 4.0×10 14 / m2 The above values are not limited to the above values, and other values not listed in the above values are also applicable.
[0016] Preferably, the Mg content in the Al-Zn alloy is ≤0.02wt%, for example, it can be 0.02wt%, 0.019wt%, 0.018wt%, 0.017wt%, 0.016wt%, 0.015wt%, 0.014wt%, 0.013wt%, 0.012wt%, 0.011wt% or 0.01wt%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0017] Preferably, the pre-embedded fluorine-containing flux comprises potassium fluoroaluminate.
[0018] Preferably, the content of pre-embedded fluorine-containing flux in the Al-Zn-based pre-embedded flux layer is 4 to 20wt%, for example, it can be 4wt%, 6wt%, 8wt%, 10wt%, 12wt%, 13wt%, 15wt%, 17wt%, 19wt% or 20wt%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0019] It is worth noting that the fluoride flux content in the Al-Zn-based pre-embedded flux layer is 4-20%. When the flux content is lower than 4%, the flux amount is insufficient, the ability to break the oxide film on the surface of the aluminum material is limited, and the brazing is poor. When the flux content is higher than 20%, too much flux not only increases the amount of flux residue after welding but also increases the material usage and manufacturing cost.
[0020] Preferably, the core layer is an aluminum alloy containing Mg and Si elements, and the concentrations of Mg and Si in the core layer are calculated based on theoretical Mg2Si. The excess Si in the core layer is ≤0.1wt% or the excess Mg in the core layer is ≤0.1wt%, and the theoretical Mg2Si is 1.3-1.8wt%.
[0021] It is worth noting that when the Si content is less than 0.5% or the Mg content is less than 0.6%, the composite material will not form enough Mg2Si phase after brazing, which will lead to insufficient yield strength after post-weld aging, and the post-weld yield strength is lower than 150MPa. When the Si content is excessive, Si will form a coarse AlFeSi phase with Fe element, reducing the post-weld yield strength of the material; Mg is the main element for improving the post-weld yield strength. After brazing, after short-term artificial aging or long-term natural aging, the post-weld yield strength can be improved; when the Mg content is excessive, the post-weld aging strength will also be reduced.
[0022] Specifically, the excess Si in the core layer is ≤0.1wt% or the excess Mg in the core layer is ≤0.1wt%, and the theoretical Mg2Si is 1.3-1.8wt%, for example, it can be 1.3wt%, 1.36wt%, 1.42wt%, 1.47wt%, 1.53wt%, 1.58wt%, 1.64wt%, 1.69wt%, 1.75wt% or 1.8wt%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable. Among them, the Si excess in the core layer is ≤0.1wt%, for example, it can be 0.1wt%, 0.09wt%, 0.08wt%, 0.07wt%, 0.06wt%, 0.05wt% or 0.04wt%, etc.; or the Mg excess in the core layer is ≤0.1wt%, for example, it can be 0.1wt%, 0.09wt%, 0.08wt%, 0.07wt%, 0.06wt%, 0.05wt% or 0.04wt%, etc.
[0023] Preferably, the core layer further includes 0.5-0.8wt% of Fe element in terms of mass percentage, for example, it may be 0.5wt%, 0.54wt%, 0.57wt%, 0.6wt%, 0.64wt%, 0.67wt%, 0.7wt%, 0.74wt%, 0.77wt% or 0.8wt%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0024] Preferably, the core layer further includes 0.1-0.3wt% of Cu element in terms of mass percentage, for example, 0.1wt%, 0.13wt%, 0.15wt%, 0.17wt%, 0.19wt%, 0.22wt%, 0.24wt%, 0.26wt%, 0.28wt% or 0.3wt%, etc., but is not limited to the listed values, and other values not listed within the range are also applicable.
[0025] Preferably, the brazing material layer is a conventional 4XXX series filler alloy, for example, any one of 4343 alloy, 4045 alloy or 4047 alloy.
[0026] Preferably, the Si content of the Al-Si filler alloy in the brazing material layer is 7-12wt%, for example, it can be 7wt%, 7.6wt%, 8.2wt%, 8.7wt%, 9.3wt%, 9.8wt%, 10.4wt%, 10.9wt%, 11.5wt% or 12wt%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0027] Preferably, the thickness of the core layer accounts for at least 90% of the thickness of the non-solder layer, for example, it can be 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97% or 98%, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0028] It is worth noting that during the brazing process, the brazing material layer of the aluminum alloy brazing composite material will melt and flow to the weld joint, while the core layer and the Al-Zn-based pre-embedded brazing flux layer will not melt. Therefore, the strength of the material after welding depends on the ratio of the core layer thickness to the (total thickness - total thickness of the brazing material layer). The core material is an aging-strengthened aluminum alloy. The greater the ratio, the higher the strength of the composite material. Those skilled in the art know that the ratio of the brazing material layer thickness to the non-brazing material layer thickness is 5 to 25:100, and a good welding effect can be obtained within this range.
[0029] Preferably, the thickness of the Al-Zn based pre-embedded solder layer is at least 1% of the thickness of the non-solder layer.
[0030] It is worth noting that the greater the thickness of the Al-Zn based pre-embedded flux layer, the longer the corrosion resistance time that can be obtained.
[0031] In a second aspect, the present invention provides a method for preparing the Al-Zn-based pre-embedded brazing flux blank for the aluminum alloy brazing composite material according to the first aspect, the preparation method comprising:
[0032] (1) Mechanically mixing Al-Zn alloy powder and fluorine-containing flux powder to obtain Al-Zn based pre-embedded powder; wherein the particle size D of the Al-Zn based pre-embedded powder is 50 10~45μm;
[0033] (2) pressing the Al-Zn-based pre-embedded powder into tablets to obtain Al-Zn-based pre-embedded tablets, wherein the tablet pressing temperature is at most 120° C.;
[0034] (3) The Al-Zn based embedded pressed sheet is arranged in the groove of the core layer to obtain an Al-Zn based embedded slab.
[0035] It is worth noting that the median D of Al-Zn based embedded powder 50 The particle size is 10-45μm. 50 When the particle size is less than 10 μm, it is difficult to press and form. 50 When the particle size is greater than 45 μm, the dislocation density is too low, which leads to the phenomenon that the weld joint of the multilayer composite material deteriorates during brazing. 50The Al-Zn based pre-embedded powder can be 10 to 45 μm. For example, the Al-Zn alloy powder disclosed in the present invention has a particle size D 50 The particle size D of the fluorine-containing flux powder is 20 to 55 μm. 50 The thickness of the sheet is 4 to 20 μm, and the sheet is compounded at a corresponding ratio. During the preparation process, those skilled in the art can adjust the molding pressure according to the target porosity requirements. As a general understanding, the porosity should not be greater than 10%, such as 10%, 9% or 8%, etc., otherwise it will lead to poor brazing. The exemplary tablet molding pressure is 10 to 50 MPa, such as 10 MPa, 20 MPa, 30 MPa, 40 MPa or 50 MPa, etc.
[0036] Specifically, the particle size D of the Al-Zn based embedded powder is 50 It is 10 to 45 μm, for example, it can be 10 μm, 14 μm, 18 μm, 22 μm, 26 μm, 30 μm, 34 μm, 38 μm, 42 μm or 45 μm, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0037] Specifically, the tableting temperature is at most 120°C, for example, 120°C, 110°C, 90°C, 80°C, 75°C, 60°C, 50°C or 25°C.
[0038] It is worth noting that when conventional pre-embedded flux hot forming technology applicable to 4XXX series aluminum alloys is used, it is usually difficult to form the dislocation density targeted by the present invention in the finished product thickness, which will cause the pre-embedded flux in the Al-Zn base to be difficult to achieve the function of breaking the film during brazing. The present invention prepares a non-filler aluminum-based pre-embedded flux layer sheet by avoiding key process parameters such as high-temperature heat treatment of existing hot forming technology, and controls a specific sheeting forming temperature.
[0039] In a second aspect, the present invention provides an aluminum alloy brazing composite material, wherein the preparation method of the aluminum alloy brazing composite material is carried out using the Al-Zn based pre-embedded brazing flux slab prepared by the preparation method of the Al-Zn based pre-embedded brazing flux slab for the aluminum alloy brazing composite material described in the first aspect.
[0040] Preferably, the preparation method comprises:
[0041] S1, placing the brazing material layer slab on the Al-Zn based embedded slab, and performing low temperature hot rolling to obtain a composite hot rolled plate;
[0042] S2, cold rolling the composite hot-rolled plate to obtain a pre-embedded composite material with a finished thickness.
[0043] Preferably, the temperature of the low-temperature hot rolling is not higher than 430°C, for example, it may be 430°C, 429°C, 428°C, 425°C, 420°C, 415°C, 410°C, 405°C or 400°C.
[0044] Preferably, the cold rolling single pass reduction is not greater than 30%, and multiple cold rolling passes may be used until the target thickness is reached, for example, 30%, 29%, 28%, 27%, 25%, 24%, 22%, 20%, 19%, 15%, 12% or 10%, etc. When the cold rolling single pass reduction is greater than 30%, it is easy to cause the dislocation density of the sheet after cold rolling to decrease.
[0045] The micron-sized Al-Zn-based embedded powder undergoes a short-term high-temperature treatment during the material preparation and subsequent brazing process. The atoms diffuse with each other, achieving metallurgical bonding and ensuring the material's processing and forming capabilities. However, although the Al-Zn-based embedded powder undergoes plastic deformation during the preparation process, the interfaces between the original particles are not completely eliminated. A large number of original interfaces hinder the slip between atoms. Dislocations are further generated during the deformation of the material, forming a high dislocation density. During the high-temperature brazing process, it acts as a diffusion channel for the molten brazing flux, allowing the molten brazing flux to quickly diffuse and enrich into the brazing layer, remove the oxide film on the surface of the brazing layer, and when the aluminum-silicon brazing alloy is melted, the brazing alloy is spread and filled smoothly under the capillary force.
[0046] It is worth noting that controlling the specific sheet forming and the subsequent hot rolling temperature and cold rolling reduction of the composite plate is the key.
[0047] During hot rolling, the material is in a dynamic recrystallization rolling state, and no new dislocations will be generated at this stage. The hot rolling reduction has little effect on the dislocation density in the Al-Zn-based pre-embedded layer. However, the hot rolling temperature cannot be too high, otherwise the powder particles in the Al-Zn-based pre-embedded sheet will be fully metallurgically bonded, and the dislocations formed by defects such as the original interface during the deformation process will be eliminated, which will reduce the dislocation density of the Al-Zn-based pre-embedded layer.
[0048] During cold rolling, the material is in a work-hardening state, the grains are elongated in the rolling direction, gradually become fibrous, and the dislocation density accumulates continuously. Therefore, on the contrary, during the cold rolling process, it is very important to control the maximum reduction of a single pass. The reason is that during cold rolling, the material is in a work-hardening state. When the reduction of a single pass is too large, the short-term large deformation will promote the recovery and recrystallization of the deformed structure in the Al-Zn-based pre-embedded layer, resulting in a decrease in the generated dislocation density. Therefore, by controlling the reduction of a single pass cold rolling, it is ensured that the composite plate will not cause a decrease in dislocation density during the cold rolling process. By controlling a relatively small reduction, the dislocation density of the Al-Zn-based pre-embedded layer is gradually accumulated, providing a necessary channel for the diffusion of the flux in the subsequent brazing process.
[0049] Preferably, the thickness of the finished embedded composite material is 0.6 to 3 mm, for example, it can be 0.6 mm, 0.9 mm, 1.2 mm, 1.4 mm, 1.7 mm, 2 mm, 2.2 mm, 2.5 mm, 2.8 mm or 3 mm, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0050] The aluminum alloy brazing composite material can be further annealed as required, and the annealing process can be freely selected according to the target state. For example, the annealing temperature is 340-400°C, and the annealing time is 2-3 hours, but it is not limited to the listed values, and other values not listed in the range are also applicable.
[0051] In a second aspect, the present invention provides a brazing method of an aluminum alloy brazing composite material, wherein the brazing method is performed using the aluminum alloy brazing composite material described in the first aspect.
[0052] Preferably, the brazing temperature is 597-603°C, for example, it can be 597°C, 598°C, 599°C, 600°C, 601°C, 602°C or 603°C, but is not limited to the listed values, and other values not listed within the range are equally applicable. The time is 3-5min, for example, it can be 3min, 3.3min, 3.5min, 3.7min, 3.9min, 4.2min, 4.4min, 4.6min, 4.8min or 5min, but is not limited to the listed values, and other values not listed within the range are equally applicable.
[0053] It is worth noting that the high dislocation density in the Al-Zn-based pre-embedded flux layer acts as a diffusion channel for the molten flux during high-temperature brazing, allowing the molten flux to quickly diffuse and enrich into the brazing material layer, removing the oxide film on the surface of the brazing material layer, and when the aluminum-silicon brazing material melts, the brazing material is smoothly spread and filled under the capillary force. The dislocations at the interface between the core layer and the Al-Zn-based pre-embedded flux layer are blocked by the generated KMgF3, which greatly reduces the ability of the Mg element to diffuse to the outside.
[0054] Compared with the prior art, the present invention has at least the following beneficial effects:
[0055] The aluminum alloy brazing composite material provided by the present invention can realize self-brazation at a brazing temperature of 600±3°C, without the need for additional application of brazing flux, thereby reducing the pollution of residual brazing flux to the battery coolant. At the same time, the weld length is above 25 μm, the post-weld aging yield strength can reach above 150 MPa, and there is no perforation in SWAAT salt spray corrosion for 40 days; and the reaction product of the Mg element and the fluorine-based brazing flux can effectively block the diffusion of the Mg element to the brazing surface, and the final surface Mg content is less than 5wt%. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 It is a schematic diagram of the aluminum alloy brazing composite material provided in Example 1 of the present invention.
[0057] Figure 2 It is the EBSD image of the Al-Zn based embedded slab B1 in the present invention.
[0058] Figure 3 It is the EBSD-KAM image of the Al-Zn based embedded slab B1 in the present invention.
[0059] Figure 4 It is a schematic diagram of a T-type brazing specimen model in the weld length test of the present invention.
[0060] In the figure, 1-core layer; 2-Al-Zn based embedded flux layer; 3-brazing material layer; 4-brazing plate. DETAILED DESCRIPTION
[0061] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0062] Core layer X1: It is an aluminum alloy containing Mg and Si elements. Calculated by mass percentage, the Mg content is 0.95wt%, the Si content is 0.6wt%, the Fe content is 0.7wt%, and the Cu content is 0.2wt%. Calculated based on theoretical Mg2Si, the Si content in the core layer is 0.05wt% in excess, and the theoretical Mg2Si is 1.5wt%. The solidus temperature is 610°C.
[0063] Core layer X2: It is an aluminum alloy containing Mg and Si elements. Calculated by mass percentage, the Mg content is 0.92wt%, the Si content is 0.48wt%, the Fe content is 0.5wt%, and the Cu content is 0.1wt%. Calculated based on theoretical Mg2Si, the core layer has an excess of 0.1wt%, and the theoretical Mg2Si is 1.3wt%. The solidus temperature is 613°C.
[0064] Core layer X3: It is an aluminum alloy containing Mg and Si elements. Calculated by mass percentage, the Mg content is 1.1wt%, the Si content is 0.59wt%, the Fe content is 0.8wt%, and the Cu content is 0.3wt%. Calculated based on theoretical Mg2Si, the core layer has an excess of 0.09wt%, and the theoretical Mg2Si is 1.6wt%. The solidus temperature is 599°C.
[0065] Solder layer Q1: 4047 alloy, wherein the Si content is 12wt% and the liquidus temperature is 581°C.
[0066] Solder layer Q2: 4045 alloy, wherein the Si content is 9.8wt% and the liquidus temperature is 595°C.
[0067] Al-Zn based pre-embedded pressed sheet Y1: The preparation method of Al-Zn based pre-embedded pressed sheet Y1 comprises:
[0068] (1) Mechanically mixing an Al-Zn alloy powder having a particle size D50 of 41 μm and a fluorine-containing flux powder to obtain an Al-Zn-based pre-embedded powder; wherein the Al-Zn alloy powder comprises 5 wt% of Zn element and 0.01 wt% of Mg element according to mass fraction, and the solidus temperature is 640°C. The particle size D50 of the Al-Zn-based pre-embedded powder is 50 The fluorine-containing flux powder is potassium fluoroaluminate, with a particle size of 3 μm and a fluorine-containing flux content of 10 wt%;
[0069] (2) At 25° C., the Al—Zn-based pre-embedded powder was pressed into tablets at a pressure of 25 MPa to obtain an Al—Zn-based pre-embedded pressed tablet Y1 with a porosity of 9%.
[0070] Al-Zn based pre-embedded pressed sheet Y2: The preparation method of Al-Zn based pre-embedded pressed sheet Y2 comprises:
[0071] (1) Mechanically mixing an Al-Zn alloy powder having a particle size D50 of 24 μm and a fluorine-containing flux powder to obtain an Al-Zn-based pre-embedded powder; wherein the Al-Zn alloy powder comprises 1 wt% Zn element and 0.02 wt% Mg element according to mass fraction, and the solidus temperature is 656°C. The particle size D50 of the Al-Zn-based pre-embedded powder is 50 The fluorine-containing flux powder is potassium fluoroaluminate, with a particle size of 3 μm and a fluorine-containing flux content of 4 wt%;
[0072] (2) At 50° C., the Al—Zn-based pre-embedded powder was pressed into tablets at a pressure of 10 MPa to obtain Al—Zn-based pre-embedded tablets Y2 with a porosity of 10%.
[0073] Al-Zn based pre-embedded pressed sheet Y3: The preparation method of Al-Zn based pre-embedded pressed sheet Y3 comprises:
[0074] (1) Mechanically mixing an Al-Zn alloy powder having a particle size D50 of 53 μm and a fluorine-containing flux powder to obtain an Al-Zn-based pre-embedded powder; wherein the Al-Zn alloy powder includes 12 wt% of Zn element by mass, Mg element is less than 0.01 wt% and is considered to be undetectable, and the solidus temperature is 613 ° C. The particle size D50 of the Al-Zn-based pre-embedded powder is 50The fluorine-containing flux powder is potassium fluoroaluminate, with a particle size of 3 μm and a fluorine-containing flux content of 20 wt%;
[0075] (2) At 120° C., the Al—Zn-based pre-embedded powder was pressed into tablets at a pressure of 50 MPa to obtain Al—Zn-based pre-embedded tablets Y3 with a porosity of 8.5%.
[0076] Al-Zn based pressed sheet YD1: The difference from Al-Zn based pre-buried pressed sheet Y1 is that the particle size of Al-Zn alloy powder is 50 The diameter of the Al-Zn alloy powder is 30 μm. No fluorine-containing flux powder is added to the Al-Zn alloy powder. The Al-Zn alloy powder is directly used for tableting in step (2). The remaining processing parameters are the same as those of the Al-Zn-based embedded tablet Y1, and the porosity is within the qualified range, which is 8%.
[0077] Al-Zn based embedded sheet YD2: The difference from Al-Zn based embedded sheet Y1 is that the content of Zn element in the Al-Zn alloy powder is 0.05wt%, the solidus temperature is 660°C, and the other processing parameters are the same as those of the Al-Zn based embedded sheet Y1, and the porosity is within the qualified range, which is 8.5%.
[0078] Al-Zn based pre-embedded sheet YD3: The difference from Al-Zn based pre-embedded sheet Y1 is that the sheet is formed by hot pressing, wherein the hot pressing temperature is 260°C, and the other processing parameters are the same as those of Al-Zn based pre-embedded sheet Y1, and the porosity is within the qualified range, which is 8.3%.
[0079] Al-Zn based pre-embedded sheet YD4: The difference from Al-Zn based pre-embedded sheet Y1 is that the particle size of Al-Zn alloy powder is 50 89 μm, so that the particle size D of the Al-Zn based embedded powder 50 The thickness of the sheet is 50 μm, and the other processing parameters are the same as those of the Al-Zn based embedded sheet Y1, and the porosity is within the qualified range, which is 9.1%.
[0080] Al-Zn based pre-embedded sheet YD5: The difference from Al-Zn based pre-embedded sheet Y1 is that the particle size of Al-Zn alloy powder is 50 12 μm, so that the particle size D of the Al-Zn based embedded powder 50 The particle size of the Al-Zn based pre-embedded pressed sheet is less than 10 μm, which makes it difficult to press and form, and the final forming fails.
[0081] Al-Zn-based embedded slab B1: The Al-Zn-based embedded pressed sheet Y1 is arranged in a groove arranged on the surface of the core layer X1 to obtain the Al-Zn-based embedded slab B1; the thickness of the Al-Zn-based embedded pressed sheet Y1 is 2.5 mm, and the thickness of the core layer X1 is 90 mm.
[0082] Al-Zn-based embedded slab B2: The Al-Zn-based embedded pressed sheet Y2 is arranged in the groove arranged on the surface of the core layer X2 to obtain the Al-Zn-based embedded slab B2; the thickness of the Al-Zn-based embedded pressed sheet Y2 is 8.8 mm, and the thickness of the core layer X2 is 80 mm.
[0083] Al-Zn-based embedded slab B3: The Al-Zn-based embedded pressing sheet Y3 is arranged in the groove arranged on the surface of the core layer X3 to obtain the Al-Zn-based embedded slab B3; the thickness of the Al-Zn-based embedded pressing sheet Y3 is 1 mm, and the thickness of the core layer X3 is 90 mm.
[0084] Al-Zn based slab BD1: The difference from Al-Zn based pre-embedded slab B1 is that Al-Zn based pressed sheet YD1 is used, and the rest is the same as Al-Zn based pre-embedded slab B1.
[0085] Al-Zn based embedded slab BD2: The difference from Al-Zn based embedded slab B1 is that Al-Zn based embedded pressed sheet YD2 is adopted, and the rest is the same as Al-Zn based embedded slab B1.
[0086] Al-Zn based embedded slab BD3: The difference from Al-Zn based embedded slab B1 is that Al-Zn based embedded pressed sheet YD3 is adopted, and the rest is the same as Al-Zn based embedded slab B1.
[0087] Al-Zn based embedded slab BD4: The difference from Al-Zn based embedded slab B1 is that Al-Zn based embedded pressed sheet YD4 is adopted, and the rest is the same as Al-Zn based embedded slab B1.
[0088] Example 1
[0089] This embodiment provides an aluminum alloy brazing composite material. Figure 1The aluminum alloy brazing composite material includes a non-brazing material layer and a brazing material layer 3 in sequence; the non-brazing material layer includes a core layer 1 and an Al-Zn-based pre-embedded brazing flux layer 2 in sequence, and the Al-Zn-based pre-embedded brazing flux layer 2 is arranged close to the brazing material layer 3. In the aluminum alloy brazing composite material, the thickness of the brazing material layer 3 accounts for 7.5%, the thickness of the core layer 1 accounts for 90%, the thickness of the Al-Zn-based pre-embedded brazing flux layer 2 accounts for 2.5%, and the thickness ratio of the brazing material layer to the non-brazing material layer (the sum of the thickness of the Al-Zn-based pre-embedded brazing flux layer and the core layer) is 0.081; the thickness of the Al-Zn-based pre-embedded brazing flux layer 2 accounts for 2.7% of the thickness of the non-brazing material layer (the sum of the thickness of the Al-Zn-based pre-embedded brazing flux layer and the core layer), the thickness of the core layer 1 accounts for 97.3% of the thickness of the non-brazing material layer (the sum of the thickness of the Al-Zn-based pre-embedded brazing flux layer and the core layer), and the dislocation density of the Al-Zn-based pre-embedded brazing flux layer 2 is 4.0×10 14 / m 2 .
[0090] The preparation method of the aluminum alloy brazing composite material comprises:
[0091] S1, prepare a solder layer blank Q1 with a thickness of 7.5 mm and an Al-Zn based embedded blank B1 with a thickness of 92.5 mm;
[0092] After placing the brazing material layer blank Q1 on the Al-Zn based pre-embedded blank B1, low temperature hot rolling is performed at 420°C to obtain a composite hot rolled plate;
[0093] S2, cold rolling the composite hot-rolled plate, wherein the cold rolling is performed in multiple passes, and the reduction amount of each pass is 25%, to obtain a finished embedded composite material F1 with a thickness of 1.8 mm.
[0094] Example 2
[0095] The present embodiment provides an aluminum alloy brazing composite material, the aluminum alloy brazing composite material includes a non-braze layer and a brazing layer in sequence; the non-braze layer includes a core layer and an Al-Zn-based pre-embedded brazing layer in sequence, and the Al-Zn-based pre-embedded brazing layer is arranged close to the brazing layer. The thickness of the brazing layer in the aluminum alloy brazing composite material accounts for 5.0%, the thickness of the core layer accounts for 85.6%, and the thickness of the Al-Zn-based pre-embedded brazing layer accounts for 9.4%, that is, the thickness ratio of the brazing layer to the non-braze layer (the sum of the thickness of the Al-Zn-based pre-embedded brazing layer and the core layer) is 0.053; the thickness of the Al-Zn-based pre-embedded brazing layer accounts for 9.9% of the thickness of the non-braze layer (the sum of the thickness of the Al-Zn-based pre-embedded brazing layer and the core layer), the thickness of the core layer accounts for 90.1% of the thickness of the non-braze layer (the sum of the thickness of the Al-Zn-based pre-embedded brazing layer and the core layer), and the dislocation density of the Al-Zn-based pre-embedded brazing layer is 3.1×10 14 / m 2 .
[0096] The preparation method of the aluminum alloy brazing composite material comprises:
[0097] S1, prepare a solder layer blank Q2 with a thickness of 4.7 mm and an Al-Zn based embedded blank B2 with a thickness of 88.8 mm;
[0098] After placing the brazing material layer blank Q2 on the Al-Zn based pre-embedded blank B2, low temperature hot rolling is performed at 430°C to obtain a composite hot rolled plate;
[0099] S2, cold rolling the composite hot-rolled plate, wherein the cold rolling is performed in multiple passes, and the reduction amount of each pass is 26%, to obtain a finished pre-embedded composite material F2 with a thickness of 3 mm.
[0100] Example 3
[0101] The present embodiment provides an aluminum alloy brazing composite material, the aluminum alloy brazing composite material includes a non-brazing material layer and a brazing material layer in sequence; the non-brazing material layer includes a core layer and an Al-Zn-based pre-embedded brazing agent layer in sequence, and the Al-Zn-based pre-embedded brazing agent layer is arranged close to the brazing material layer. In the aluminum alloy brazing composite material, the thickness of the brazing material layer accounts for 9.0%, the thickness of the core layer accounts for 90%, and the thickness of the Al-Zn-based pre-embedded brazing agent layer accounts for 1.0%, that is, the thickness ratio of the brazing material layer to the non-brazing material layer (the sum of the thickness of the Al-Zn-based pre-embedded brazing agent layer and the core layer) is 0.099; the thickness of the Al-Zn-based pre-embedded brazing agent layer accounts for 1.1% of the thickness of the non-brazing material layer (the sum of the thickness of the Al-Zn-based pre-embedded brazing agent layer and the core layer), the thickness of the core layer accounts for 98.9% of the thickness of the non-brazing material layer (the sum of the thickness of the Al-Zn-based pre-embedded brazing agent layer and the core layer), and the dislocation density of the Al-Zn-based pre-embedded brazing agent layer is 2.5×10 14 / m 2 .
[0102] The preparation method of the aluminum alloy brazing composite material comprises:
[0103] S1, prepare a solder layer blank Q2 with a thickness of 9 mm and an Al-Zn based embedded blank B3 with a thickness of 91 mm;
[0104] After the brazing material layer blank Q2 is placed on the Al-Zn based pre-embedded blank B3, low temperature hot rolling is performed at 410°C to obtain a composite hot rolled plate;
[0105] S2, cold rolling the composite hot-rolled plate, wherein the cold rolling is performed in multiple passes, and the reduction amount of each pass is 30%, to obtain a finished pre-embedded composite material F3 with a thickness of 0.6 mm.
[0106] Comparative Example 1
[0107] This comparative example provides an aluminum alloy brazing composite material, which is different from Example 1 only in that an Al-Zn-based substrate blank BD1 is used, and the rest is the same as Example 1. The dislocation density of the final Al-Zn-based brazing flux layer is 3.5×10 14 / m 2 .
[0108] Comparative Example 2
[0109] This comparative example provides an aluminum alloy brazing composite material, which is different from Example 1 only in that an Al-Zn-based pre-embedded plate blank BD2 is used, and the rest is the same as Example 1. The final dislocation density of the Al-Zn-based pre-embedded flux layer is 2.62×10 14 / m 2 .
[0110] Comparative Example 3
[0111] This comparative example provides an aluminum alloy brazing composite material, which is different from Example 1 only in that an Al-Zn-based pre-embedded plate blank BD3 is used, and the rest is the same as Example 1. The final dislocation density of the Al-Zn-based pre-embedded brazing flux layer is 9.7×10 13 / m 2 .
[0112] Comparative Example 4
[0113] This comparative example provides an aluminum alloy brazing composite material, which is different from Example 1 only in that an Al-Zn-based pre-embedded plate blank BD4 is used, and the rest is the same as Example 1. The final dislocation density of the Al-Zn-based pre-embedded flux layer is 6.6×10 13 / m 2 .
[0114] Comparative Example 5
[0115] This comparative example provides an aluminum alloy brazing composite material, which is different from Example 1 only in that the temperature of low-temperature hot rolling is 450°C, and the rest is the same as Example 1. The final dislocation density of the Al-Zn-based pre-embedded brazing flux layer is 7.8×10 13 / m 2 .
[0116] Comparative Example 6
[0117] This comparative example provides an aluminum alloy brazing composite material, which is different from Example 1 only in that the single pass reduction of cold rolling is 35%, and the rest is the same as Example 1. The final dislocation density of the Al-Zn-based pre-embedded flux layer is 1.4×10 14 / m 2 .
[0118] Application Example 1
[0119] This application example provides a brazing method for the aluminum alloy brazing composite material in Example 1, wherein the brazing method is performed using the weld length detection process in the test method, wherein the brazing temperature is 600° C. and the brazing time is 4 minutes.
[0120] Application Example 2
[0121] This application example provides a brazing method for the aluminum alloy brazing composite material in Example 2, wherein the brazing method is performed using the weld length detection process in the test method, wherein the brazing temperature is 597° C. and the brazing time is 5 minutes.
[0122] Application Example 3
[0123] This application example provides a brazing method for the aluminum alloy brazing composite material in Example 3, wherein the brazing method is performed using the weld length detection process in the test method, wherein the brazing temperature is 603° C. and the brazing time is 3 minutes.
[0124] Application Comparative Example 1
[0125] This application comparative example provides a brazing method for the aluminum alloy brazing composite material in comparative example 1, which is different from application example 1 only in that an equal amount of brazing flux as that in embodiment 1 is added during brazing.
[0126] Application Comparative Examples 2 to 6
[0127] Application Examples 2 to 6 provide a brazing method for the aluminum alloy brazing composite material in each of Comparative Examples 2 to 6, and the rest is the same as Application Example 1.
[0128] Test method:
[0129] 1. Solid / liquid phase temperature: The solid / liquid phase temperature of the sample was measured using a German Netzsch STA449F5 synchronous thermal analyzer. The sample size was 15-20 mg, the measurement temperature was from room temperature to 750°C, and the heating rate was 10°C / min.
[0130] 2. Dislocation density: Al-Zn-based pre-embedded flux layer under the finished product thickness of the test object. The sample was tested by using the Oxford C-nano electron backscatter diffraction detector (EBSD) equipped with the German Zeiss SIGMA300 field emission scanning electron microscope to obtain the KAM map. The dislocation density of each pixel is exported by AZTEC software, and then the dislocation density of all pixels on the scanned surface is added and divided by the number of pixels to obtain the dislocation density of this surface.
[0131] 3. Corrosion time: The brazing plates after simulated brazing were cut into 60mm×100mm specimens and subjected to salt spray corrosion tests for different days according to ASTM-G8:A3 standard. After cleaning the surface of the salt spray corroded samples, three locations with the largest surface corrosion pits were taken from each sample, and metallographic specimens were prepared according to conventional methods. The cross-sections were subjected to metallographic observation, and the days when perforation first appeared were used as the corrosion resistance days of the samples.
[0132] 4. Yield strength after brazing and aging: Simulated brazing: Raise the sample to the target brazing temperature at a heating rate of 30°C / min, keep it warm for the target time, and take it out for air cooling. Aging process: Keep the sample after simulated brazing at 170°C for 12 hours. The mechanical properties of the aluminum alloy composite sheet after simulated brazing and aging were tested in accordance with the method disclosed in GB / T228.1-2010 "Metallic Material Tensile Test Part 1: Room Temperature Test Method". The testing instrument is a ZWICK universal material testing machine. The test indicators are the specified plastic extension strength (Rp0.2) and elongation after fracture (A). The test uses a 50mm gauge length.
[0133] 5. Weld length: Cut the aluminum alloy brazing composite material into 25mm×60mm samples and place them flat on the test bench. Figure 4 The 25mm×60mm AA3003 alloy was placed vertically on the brazing plate to form a T-shaped sample. The T-shaped sample was placed in a 100mm quartz tube furnace for simulated brazing. Nitrogen was used to protect the quartz tube furnace. Simulated brazing process: the temperature was raised to 600±3℃ at a heating rate of 30℃ / min and then kept warm for 3-5min. The sample was taken out and air-cooled to room temperature to obtain a brazing plate after simulated brazing. The length of the weld of the T-shaped sample after brazing was counted.
[0134] 6. Surface Mg content: The brazed samples were cut into 10 mm × 10 mm sizes and scanned with an Oxford energy dispersive spectrometer (EDS) equipped with a German Zeiss SIGMA300 field emission scanning electron microscope at 100X field of view to obtain the surface Mg content of the samples. Three fields of view were tested for each sample and the average value was taken.
[0135] 7. Porosity: Samples of Al-Zn-based embedded powder compacts are taken, and the sample size is about 10-20mm. According to the conventional metallographic sample preparation process, the samples are coarsely ground, finely ground, coarsely polished and finely polished to obtain metallographic samples with mirror effects. The surface of the sample after grinding and polishing is observed using a metallographic microscope. At a magnification of 100 times, three fields of view are randomly photographed to obtain three 100-fold metallographic photos. Image-Pro Plus image processing software is used to analyze the metallographic photos, and the percentage of the area of the holes in a single photo to the entire photo area is counted, which is the porosity. The average porosity of the three photos is the porosity of the compact.
[0136] The EBSD image of Al-Zn based embedded slab B1 is shown in Figure 2 As shown, the EBSD-KAM of Al-Zn based embedded slab B1 is shown in Figure 3 ,from Figures 2-3 It can be seen that there are obvious dislocations in the Al-Zn based embedded slab B1.
[0137] The test results in the above application example are shown in Table 1.
[0138] Table 1
[0139]
[0140]
[0141] From Table 1, we can see the following points:
[0142] (1) It can be seen from Application Examples 1 to 3 that the aluminum alloy brazing composite material provided by the present invention has a dislocation density of 2.5 to 4.0×10 14 / m 2 For the Al-Zn-based pre-buried flux layer of the Al-Zn alloy with a high solidus temperature, the flux can reach the brazing material layer through the dislocation channel to achieve a better brazing effect, and the final weld length is more than 30μm, and the yield strength after aging after brazing is more than 175MPa, and there is no perforation in SWAAT salt spray corrosion for more than 40 days; and the reaction product of Mg element and fluorine-based flux can effectively block the diffusion of Mg element to the brazing surface, and the final surface Mg content is less than 5wt%;
[0143] (2) Effect of using Al-Zn alloy: By comparing Application Example 1 and Application Comparative Example 2, it can be seen that the Al-Zn alloy containing a relatively low Zn content is used in Application Comparative Example 2, and the final corrosion resistance is significantly reduced compared with Application Example 1;
[0144] (3) Advantages of pre-embedded brazing flux: By comparing Application Example 1 with Application Comparative Example 1, it can be seen that the yield strength after brazing and aging of the brazing in Application Comparative Example 1 is significantly reduced, and the weld length is significantly shortened, compared with the pre-embedded brazing flux in Application Example 1.
[0145] (4) Effect of dislocation density: By comparing Application Example 1 with Application Comparative Examples 3 to 6, it can be seen that in Application Comparative Example 3, hot pressing is used, and in Application Comparative Example 4, the particle size D of the Al-Zn based pre-embedded powder is 50 It is 45μm. The hot rolling temperature in comparative example 5 is too high, and the single cold rolling pressure in comparative example 6 is too high, which leads to a small dislocation density of the final Al-Zn based pre-embedded flux layer. In the final brazing process, the dislocation channels available to the flux are reduced, the weld length is reduced, and the brazing performance is reduced.
[0146] The present invention illustrates the detailed features of the present invention through the above embodiments, but the present invention is not limited to the above detailed features, that is, it does not mean that the present invention must rely on the above detailed features to be implemented. Those skilled in the art should understand that any improvement to the present invention, equivalent replacement of the technical features selected by the present invention, addition of auxiliary technical features, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. An aluminum alloy brazing composite material, characterized in that: The aluminum alloy brazing composite material comprises a non-brazing material layer and a brazing material layer in sequence; the non-brazing material layer comprises a core layer and an Al-Zn-based pre-embedded brazing flux layer in sequence, and the Al-Zn-based pre-embedded brazing flux layer is arranged close to the brazing material layer; The Al-Zn based pre-buried flux layer comprises an Al-Zn alloy and a fluorine-containing flux; The Al-Zn alloy includes 1-12 wt% of Zn element according to mass fraction, the Al-Zn based pre-embedded flux layer has dislocations, and the dislocation density of the Al-Zn based pre-embedded flux layer is 2.5-4.0×10 14 / m 2 ; The non-solder layer cannot be melted during brazing.
2. The aluminum alloy brazing composite material according to claim 1, characterized in that: The Mg content in the Al-Zn alloy is ≤0.02wt%.
3. The aluminum alloy brazing composite material according to claim 1 or 2, characterized in that: The fluorine-containing flux includes potassium fluoroaluminate; The content of fluorine-containing flux in the Al-Zn-based pre-embedded flux layer is 4-20wt%.
4. The aluminum alloy brazing composite material according to any one of claims 1 to 3, characterized in that: The core layer is an aluminum alloy containing Mg and Si elements. The concentrations of Mg and Si in the core layer are calculated based on theoretical Mg2Si. The excess Si in the core layer is ≤0.1wt% or the excess Mg in the core layer is ≤0.1wt%, and the theoretical Mg2Si is 1.3-1.8wt%.
5. The aluminum alloy brazing composite material according to any one of claims 1 to 4, characterized in that: The thickness of the core layer accounts for at least 90% of the thickness of the non-solder layer.
6. The aluminum alloy brazing composite material according to any one of claims 1 to 5, characterized in that: The thickness of the Al-Zn based pre-embedded solder layer is at least 1% of the thickness of the non-solder layer.
7. A method for preparing the Al-Zn based pre-embedded brazing flux slab for aluminum alloy brazing composite materials according to any one of claims 1 to 6, characterized in that: The preparation method comprises: (1) Mechanically mixing Al-Zn alloy powder and fluorine-containing flux powder to obtain Al-Zn based pre-embedded powder; wherein the particle size D of the Al-Zn based pre-embedded powder is 50 10~45μm; (2) pressing the Al-Zn-based pre-embedded powder into tablets to obtain Al-Zn-based pre-embedded tablets, wherein the tablet pressing temperature is at most 120° C.; (3) The Al-Zn based embedded pressed sheet is arranged in the groove of the core layer to obtain an Al-Zn based embedded slab.
8. A method for preparing an aluminum alloy brazing composite material, characterized in that: The preparation method is carried out using the Al-Zn-based pre-embedded brazing flux slab prepared by the preparation method of the Al-Zn-based pre-embedded brazing flux slab for aluminum alloy brazing composite materials according to claim 7; The preparation method comprises: S1, placing the brazing material layer slab on the Al-Zn based embedded slab, and performing low temperature hot rolling to obtain a composite hot rolled plate; S2, cold rolling the composite hot-rolled plate to obtain a pre-embedded composite material with a finished thickness.
9. The preparation method according to claim 8, characterized in that: The temperature of the low temperature hot rolling is not higher than 430°C; And / or, the cold rolling has a single pass reduction of no more than 30%.
10. A brazing method for aluminum alloy brazing composite materials, characterized in that: The brazing method is carried out using the aluminum alloy brazing composite material according to any one of claims 1 to 6; The brazing temperature is 597-603° C. and the brazing time is 3-5 minutes.
Citation Information
Patent Citations
Aluminum alloy composite board
CN114670510A
Cited By
Aluminum alloy composite material suitable for brazing surface structure containing fine grain area and brazing method and welding finished product of aluminum alloy composite material
CN120502803A
Brazing flux-embedded aluminum alloy brazing filler metal plate blank and preparation method thereof, brazing flux-embedded composite aluminum alloy brazing plate strip and preparation process and application thereof
CN121179078A
Aluminum alloy brazing material, preparation method thereof, brazing sheet and radiator
CN121892915A
Aluminum alloy brazing material and method of making same, brazing sheet and heat sink
CN121892915B